Morphological and Genetic Variation in Three Populations of Hoplobatrachus tigerinus from Bangladesh (Progressive Agriculture, 2013)
In order to investigate the morphological and genetic variation of Indian bullfrog Hoplobatrachus tigerinus, live samples were collected from three populations located in Khulna (southern part), Char Nilokhia and Netrokona (central part) in Bangladesh. The proportions of head length and head width (HL : HW), eye length and tympanum diameter (EL:TD), head length and snout length (HL : SL), internarial space and interorbital distance (IN:IOD) and internarial space and distance from nostril to tip of snout (IN:NS) of the Khulna population were significantly higher (p